PEMBERDAYAAN KADER POSYANDU SEBAGAI KADER KESEHATAN GIGI MELALUI KEGIATAN USAHA KESEHATAN GIGI DAN MULUT MASYARAKAT DESA (UKGMD) - Ulliana, ulliana; Nurwanti , Widi; Sulistiani, Silvia; Puspitawati, Yuli (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2023)
Community Dental Health Efforts is an educative approach that aims to increase theability and participation of the community in dental health maintenance, by integratingpromotive, preventive dental health efforts. This activity needs to be carried out toincrease awareness, willingness, ability and participation of the community / family in themaintenance of dental health. The purpose of cadre empowerment activities is toincrease the knowledge of dental health cadres. The method of cadre empowermentactivities is carried out through training on 20 cadres of the Raflesia Posyandu. Theresults of the analysis of the average value of knowledge of dental health cadres for thecadre pre-test were 9,45 while the post test was 9,65. Based on the average difference,it shows 0,20, which means that cadre empowerment is effective in increasing theknowledge of dental health cadres.